Investigating the expression of genes and proteins in Glioblastoma during hypoxia - Monteiro, Ana Rita Alves Pereira de Ferreira (2019)
Glioblastoma multiforme (GBM), grade IV Astrocytoma, is the most common and deadly form of brain cancer. Despite the low incidence rate (3.2 per 100.000 people), patient’s median survival is only 14 months. Notwithstanding all new diagnostic tools, GBM remains a therapeutic challenge, being extremely difficult to prevent recurrence. Therefore, it is essential to conduct research in order to understand the molecular pathways in the core of GBM aggressiveness and swift evolution. GBM is often characterized by hypoxic regions where oxygen levels are extremely low. As a natural consequence of tumour growth and expansion, some areas of the tumour become distanced from the blood vessels and consequently, from the oxygen supply. In such a critical environment, cells activate pro-survival and malignancy mechanisms such as the metabolic switch, invasion and angiogenesis. Hence we investigated the expression of genes featuring these survival mechanisms and identified a panel of hypoxia-driven-malignancy markers. To conduct this study, two GBM patient´s biopsy-derived cell lines (UP-029 and SEBTA-023) were used and cultured under hypoxic conditions for a selected set of time-points (time-course). To characterize the hypoxic response of these cells, hypoxia profiler microarrays were ran for normoxia, 6 and 48 hours of hypoxia (1% O2). Once identified the induced and repressed genes, these were analyzed and validated through qRT-PCR assays. Finally, western-blot analysis was performed to detect target proteins and correlate with the previously obtained gene expression data. Our study validated ANGPTL4, PIGF, VEGFA, GLUT1, PFKB4, PFKB3, BNIP3, DDIT4, NDRG1 and CAIX genes as relevant in GBM’s hypoxia-mediated response. We also pointed out MXI1, HNF4A genes as likely significant factors in GBM hypoxia. Furthermore, we hypothesize PFKB3 as an adaptive resistance marker in GBM and the repression of TFRC as required mechanism for GBM progression.